Cultivo hidropônico de mini melancia em substrato com uso de água salobra - SILVA, Andrey Thyago Cardoso Santos Gomes da (2018)
The water quality is a very important factor to obtain a good productivity, which makes necessary the due knowledge of its characteristics and possible interactions with the plants. Melancholy is a moderately salt-sensitive plant, exhibiting a 13% decrease in its yield from the threshold salinity of 2.5 dS m-1. However, the yield information of the watermelon under brackish conditions in hydroponic farming systems is still scarce. In view of the above, the objective of this work was to evaluate the effect of the use of brackish water and the time of exposure of the plants to the salinity on the agronomic and physiological aspects of the mini watermelon culture. The experiment was conducted in a greenhouse at the Department of Agricultural Engineering of the Federal Rural University of Pernambuco - UFRPE. The effects of the use of brackish water in the hydroponic cultivation of mini watermelon cv. Beni-Kodama studying two sources of variation: irrigation water salinity (CE = (0.1, 1.47, 2.97, 4.5, 6.04, 7.57 dS m-1) and time (65 and 81 days of exposure to nutrient solution), as well as the production and quality aspects of the mini watermelon fruits, as well as the gas exchange at three different times during the cycle The water salinity of irrigation water provided linear decreases in the yield and quality of the mini-watermelon cv. Beni-Kodama fruits, as well as in the gas exchange process, with respect to the time of exposure in which the plants were submitted only in commercial productivity. However, the gas exchange of the mini watermelon plants was influenced by this factor, especially in the evaluation performed at 45 DAT.